Numerical analysis of varies geometries on dynamic analysis on the gravity platform - Rezaei, Tina; Mohammadi, Atefeh Mosahebi; Mina, Elham; Reza Kavianpour, Mohammad (Innovaciencia, 2019)
On Gravity platform Dynamic Response is a support structure held in place by gravity. Given that the gravity platforms are supported by the sea bed but not attached to the ground, the motion of them is known as a rocking fluctuation. During the fluctuations, the platform maybe overturned if the angle is large. In this study, using Ansys Aqwa hydrodynamic software and analytical methods with regard to the performance, the dynamic interaction of platform’s geometry on hydrodynamic forces have been simulated. The objective of this study was to analyze the hydrodynamic parameters of the sea and rocking fluctuations of gravity platforms under the impact of regular wave’s moment considering the soil mechanics and hydrodynamic features of the structure. In order to achieve the objective the hydrodynamic forces using numerical simulations and analytical methods for one column and three hollow columns platforms were analyzed. Finally, responses of the platform to irregular waves were studied using numerical simulation. The results showed that with the increasing of the depth, the impact of wave’s force and moment on the base of platform are reduced through exponential relationship. The reductions are due to the effective depth that is equal to half the wave length. The results suggest that the response of the rocking motion of gravity platform shows significant changes in relation to height and wavelength. Based on the curves fitted to the data of the fluctuation angle, sustainability of the platform in the rocking motion can be thoroughly and completely investigated.